2022
DOI: 10.1016/j.mineng.2021.107312
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical codeposition of arsenic from acidic copper sulfate baths: The implications for sustainable copper electrometallurgy

Abstract: Copper producers face increased demand associated with increasing complexity in feedstock composition, including high amounts of impurity metals. In this work, linear sweep voltammetry was used to study the electrodeposition behavior of copper and arsenic, define strategies for the production of grade A copper, and the removal of arsenic from complex electrolytes. Our results show that the copper concentration is a key parameter to control in the electrodeposition process. The continuous deposition of arsenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The electrodeposition route is an electrometallurgical route, which is also used in metal recovery [12 -14]. Brar et al [12] overviewed integrated bioleaching and redox process for copper recovery from waste resources, while Verbruggen et al [13] reported arsenic codeposition from acidic copper sulfate solution using linear sweep voltammetry, and Whitworth et al [14] reviewed minerals processing, metal extraction, and metal recovery from mining wastes due to high economic demand.…”
Section: Electrodeposition Route For Pb Precipitation In Electrochemi...mentioning
confidence: 99%
“…The electrodeposition route is an electrometallurgical route, which is also used in metal recovery [12 -14]. Brar et al [12] overviewed integrated bioleaching and redox process for copper recovery from waste resources, while Verbruggen et al [13] reported arsenic codeposition from acidic copper sulfate solution using linear sweep voltammetry, and Whitworth et al [14] reviewed minerals processing, metal extraction, and metal recovery from mining wastes due to high economic demand.…”
Section: Electrodeposition Route For Pb Precipitation In Electrochemi...mentioning
confidence: 99%
“…Two main demands are driving this process to its limits. Primary, the need for urban mining, introducing different feed material into the process [2,3]. Secondary, the pressure to increase productivity.…”
Section: Introductionmentioning
confidence: 99%
“…These anodes contain impurities from ore concentrates, which are incorporated in the electrolyte along with copper. Elements of concern include As, Sb, and Bi since their presence can negatively affect the final quality of the copper cathode (Arbizu et al, 2010;Artzer et al, 2018;Verbruggen et al, 2022a;Verbruggen et al, 2022b). Consequently, control of such impurities in the electrolyte is of major importance.…”
Section: Introductionmentioning
confidence: 99%